2008
DOI: 10.3171/ped/2008/2/7/042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of posterior fossa decompression with and without duraplasty for the surgical treatment of Chiari malformation Type I in pediatric patients: a meta-analysis

Abstract: Object Surgery for Chiari malformation Type I (CM-I) is one of the most common neurosurgical procedures performed in children, although there is clearly no consensus among practitioners about which surgical method is preferred. The objective of this meta-analysis was to compare the outcome of posterior fossa decompression with duraplasty (PFDD) and posterior fossa decompression without duraplasty (PFD) for the treatment of CM-I in children. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
162
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(178 citation statements)
references
References 24 publications
6
162
0
4
Order By: Relevance
“…In general, pediatric patients have a better response to PFD than adults [5], implying that the more pediatric patients recruited for a study, the better the surgical outcome. Different surgical procedures might decompress the cerebellar tonsils to different extents or even exert a direct effect on the syrinx, resulting in different rates of significant syrinx improvement [4,8,[20][21][22][23]. Variability in the definition of significant improvement also may have led to contrary results among previous reports.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In general, pediatric patients have a better response to PFD than adults [5], implying that the more pediatric patients recruited for a study, the better the surgical outcome. Different surgical procedures might decompress the cerebellar tonsils to different extents or even exert a direct effect on the syrinx, resulting in different rates of significant syrinx improvement [4,8,[20][21][22][23]. Variability in the definition of significant improvement also may have led to contrary results among previous reports.…”
Section: Discussionmentioning
confidence: 93%
“…Results showed that syrinx improvement occurred mainly within 6 months and continued at a slow rate within 6 years after posterior fossa decompression [12]. Several factors, such as sex, preoperative size and syrinx length, have been reported as predictors of better surgical outcome after PFD [4,5,20]. Badie et al [27] reported that female patients have a better response to PFD than male patients because female patients have a lower posterior fossa volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,10,46 Despite only 70% of our patients showing radiographic improvement of the syrinx, 100% had initial improvement postoperatively and 88% remained asymptomatic or with minimal symptoms at last follow-up. These results are similar to the study by Wetjen et al, where at 6 months after PFD with dural opening, 96% of the patients experienced some degree of clinical improvement while only 86% had radiographic improvement of the syrinx; after 2 years, 68% remained mildly symptomatic even though 100% had radiographic improvement of the syrinx.…”
Section: Discussionmentioning
confidence: 99%
“…4,11,25,26,32,35,42 High rates of radiographic syrinx improvement have been reported after PFD with dural opening in pediatric CM-I, with symptom resolution often occurring prior to syrinx resolution and scoliosis improvement often occurring after. [1][2][3][4][5][6][7][8][10][11][12][15][16][17]20,26,27,[29][30][31][32][33][34][35]42,44 In part because syrinx improvement has been noted to occur in the majority of 17,19,36,39 At the 2006 American Society of Pediatric Neurosurgeons meeting, for example, a survey of 50% of the membership demonstrated that for children with a symptomatic CM-I and syrinx, only 4% would perform nondural opening surgery and another 4% would use ultrasound to guide whether to add duraplasty, with the vast majority opting for duraplasty with or without tonsillar resection. 36 However, controversy exists over whether the dura must be opened for successful surgery for pediatric CM-I with or without a syrinx, with good clinical outcomes being reported for a variety of methods.…”
Section: Discussionmentioning
confidence: 99%